PHYSICAL AND MECHANICAL PROPERTIES OF NON-GENINED SEEDS AND THEIR FIBROUS COVER - Khamit Isaxonov; Akramjon Sarimsakov; Soxib Rejabboev (Web of Journals Publishing, 2024)
The purpose of this work is to find and develop the optimal shape of the working chamber of the catcher and its working elements, as well as their influence on the fiber yield and the catching effect. For this purpose, an experimental setup was developed and the processes of trapping under-ginned seeds were studied.
Keywords: cotton, seed, fiber, sorter, mesh surface, fine dirt, lint, fraction, damage, productivity, hairiness.